2017
DOI: 10.1007/s00520-017-3988-x
|View full text |Cite
|
Sign up to set email alerts
|

Extended nursing for the recovery of urinary functions and quality of life after robot-assisted laparoscopic radical prostatectomy: a randomized controlled trial

Abstract: PurposeThe purpose of this work is to explore the effects of continuing nursing care intervention on postoperative urinary control and quality of life among patients with prostate cancer.MethodsThis was a single-center, parallel, and randomized controlled trial that was carried out at the Department of Urology, the First Affiliated Hospital of Anhui Medical University, China. The participants underwent robot-assisted laparoscopic radical prostatectomy (RARP) between October 2014 and April 2016. The patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 31 publications
0
22
0
4
Order By: Relevance
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
“…In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set. As for the language of the articles, 16 were published in English, (5,6,8,11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) one in Spanish (7) and one in Portuguese. (23) As for the country where the study was developed, three were developed in Spain, followed by the United States, United Kingdom, Italy, Australia and China, with two studies each, and Brazil, Denmark, Sweden, Norway and The Netherlands, with one study in each country.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations